MONETARY, FISCAL AND GREEN TRADE INDICATORS IN INDONESIA - Dewi Mahrani Rangkuty; Rusiadi; Lia Nazliana Nasution; Wahyu Indah Sari; Rapita Damanik (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2024)
Monetary policy, fiscal policy, and green trade are distinct yet interconnected elements that influence the economy. In this research, research is conducted by utilising studies which are similar or related. After collecting various literature related to the study under study, the researcher makes observations then the object of research is explored through various library information both from books, natural journals, digital data, documents and so on in order to analyse monetary, fiscal and green trade indicators in Indonesia. Governments might use fiscal measures, such as tax incentives for green technologies, to promote environmentally friendly trade practices. Central banks can support green trade by considering environmental risks in their financial stability assessments and potentially incorporating sustainability criteria into their monetary policy frameworks.